A method for determining the median line of measured cylindrical and conical surfaces. (25th June 2015) - Janecki, Dariusz; Zwierzchowski, Jarosław
Abstract: The paper presents a novel method for the determination of the median line of the cylindrical and conical surfaces. This method can be incorporated into virtually any cylindricity measurement strategy, including the bird-cage strategy and the helical line strategy. In the study, a median line was determined by minimizing the functional made up of two components. The form of the first component results from the classic definition of the median line provided in the corresponding standard. The other, termed the bending energy, is responsible for ensuring appropriate smoothness of the median line. In order to solve this variational problem, the median line was approximated by means of linear combination of cubic B-spline functions. A simulation and experiments were conducted to establish the suitability of the algorithm developed for the determination of the median line using the helical-line and the cross-section measurement strategy.